Brazilian women in paralympic sports: uncovering historical milestones in the summer paralympic games - Fabricio dos Santos, L. G. T.; dos Santos Alves, I.; Feliciano, N. F.; Ortuño Torres, A. A.; Correia de Campos, L. F. C.; Tanure Alves, M. L. (Adapted Physical Activity Quarterly, 2024)
The journey of Brazilian female Paralympians transcends mere statistical increases in women`s participation. Behind the modest athlete growth lies the reality of women who are doubly marginalized by the intersection of gender and disability in an arena tailored for able-bodied men. Our study aimed to catalyze critical discourses surrounding the historical trajectory of Paralympic women`s sports. Through a comprehensive documentary analysis based on the Brazilian Paralympic Committee`s official documents from 1976 to 2021, we sought to shed light on this complex scenario. Numerically, Brazil`s representation comprised 229 women who, predominantly, had physical impairments and engaged in individual sports. In addition to a sporting legacy deeply entrenched in physical rehabilitation with limited opportunities for team-based sports, we observed negative influences stemming from ableist and sexist narratives. A thorough investigation into Paralympic milestones revealed a multitude of social barriers and highlighted the significant impact of societal changes in reshaping athletic opportunities and challenging traditional stereotypes.